Death Penalty and Human Rights in Indonesia - Purba, Nelvitia; Tanjung, Ali Mukti; Pramono, Rudy; Purwanto, Agus (International Journal of Criminology and Sociology, 2022)
The aim of the research was to investigate whether the applicable death penalty in the Criminal Laws of Republic of Indonesia violates the human rights or not. To achieve the objectives of the research, both legal research and social-legal research method were used. Then, the respondents of the research were the representative supreme courts, official commissions, law experts, religious leaders and non-governmental organization. Depth interview and document study were chosen as data sources of the research, then, interview guidelines, note-taking, and voice recorder were used to be the instruments of the research. Death penalty is not contradictory with human rights as stated in Presidential Regulation No 2 of 1964 discussing the death penalty in Indonesia is applicable for those who commit serious crimes, namely; murder, drug possession, terrorist, and corruption. It is also corresponding to International Covenant on Civil and Political Rights, Article 7 Verse (2) – (6), which is stated that death penalty must be performed in proper methodology without both imprisonment for years and mental suffering. Death penalty is legally stated in Indonesia law that it is not recognized as cruel action in which the death penalty have never been resulting both physical and psychological pain as well as stated in Covenant and Political Right.